MANAGEMENT OF THE ACTIVITIES OF NON-GOVERNMENTAL BUSINESS SUPPORT ORGANIZATIONS - SMOLYCH, Dariia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article considers the main areas of management of non-governmental organizations: strategic planning; program development; financial management; human resources management; implementation of projects; involvement of interested parties; communications and advocacy; impact assessment. It has been established that the management process in non-governmental business support organizations is dynamic and operational, aimed at adapting to changing business needs. Effective governance ensures that these organizations can effectively fulfill their mission of supporting business and promoting sustainable economic development and prosperity. The components of the management of a non-governmental business support organization are characterized.The peculiarities of managing the activities of non-governmental business support organizations through the prism of taking into account the interests of members and stakeholders in the management of such organizations are highlighted. The typical organizational structure of non-governmental business support organizations was studied. Despite the fact that the structure may differ depending on the size, activities and goals of a specific non-governmental business support organization, as a rule, it consists of such components as: senior management, executive management and functional departments, the key aspects of their work are considered.Documents defining management in non-governmental business support organizations were considered, in particular: charter; internal regulations (determine relations with members); principles, rules and policies; strategic plan («road map» of the organization's functioning); annual budget The resource provision of non-governmental business support organizations and the management aspect of such provision are characterized, namely: management of material, human, and financial resources; time, technology and information management; risk management; strategic management.
Keywords: non-governmental business support organizations; management; the organizational structure; resource provision